Fenomenologia [„Encyklopedia Brytyjska”: wersja I] - Husserl, Edmund (Filozofia Publiczna i Edukacja Demokratyczna, 2015)
This text is the ‘first draft” (erster Entwurf) of Edmund Husserl’s article for the 14th edition of the Encyclopedia Britannica. The text had four versions (A, B, C, D) and it received its final version after many months of work. This ‘first draft’ has a cognitive value as it reflects Husserl’s spontaneous intuitions about understanding of phenomenology and a phenomenological method in the vein of transcendental philosophy, which he has created, developed, improved and on and on modified.